Association of lifestyle modification with the development of cardiovascular disease in gastric cancer patients who underwent gastrectomy: A nationwide population‐based study - Bokyung Kim; Kyungdo Han; Soo‐Jeong Cho (Cancer Medicine)
Abstract Background While cancer patients are at an increased risk of cardiovascular disease (CVD), the role of modifiable risk factors remains poorly understood. This study investigated whether lifestyle modifications affect CVD development in gastric cancer patients who undergo surgery. Methods Using data from the Korean National Health Insurance Service (NHIS), gastric cancer patients who underwent surgery from 2010 to 2017 were identified. Lifestyle behaviours, surveyed within 2 years before and after surgery were analysed. Incident CVD, defined as a composite of myocardial infarction and stroke, was compared among subgroups of lifestyle behaviour changes. Results Among 22,211 gastrectomy patients, 628 (2.8%) developed CVD (5.68/1000 person‐years). Persistent smokers (HR: 1.72, 95% CI: 1.33–2.22) and new smokers (HR: 1.85, 95% CI: 1.04–3.30) faced higher CVD risks than non‐smokers, with an especially pronounced risk in persistent‐smoking females (HR: 3.89, 95% CI: 1.20–12.62). Smoking cessation showed no significant risk difference compared to non‐smokers (HR: 1.16, 95% CI: 0.93–1.43). Female new drinkers had a higher CVD risk than non‐drinking females (HR: 2.89, 95% CI: 1.06–7.88), while men did not show such association. Changes in physical activity, when compared to physical inactivity, were not associated with CVD risk. Conclusion Gastric cancer patients who smoked after surgery were more likely to develop CVD irrespective of their prior smoking status, with a notable vulnerability in persistent female smokers. Smoking cessation could potentially mitigate CVD risk to levels observed in non‐smokers. Alcohol intake should be avoided following surgery, especially for female gastric cancer patients.